2016
DOI: 10.1097/cad.0000000000000418
|View full text |Cite
|
Sign up to set email alerts
|

Suberanilohydroxamic acid (vorinostat) synergistically enhances the cytotoxicity of doxorubicin and cisplatin in osteosarcoma cell lines

Abstract: Osteosarcoma is the most common primary bone cancer in children and is a highly malignant disease, in which 25% of patients present with metastasis at diagnosis. Considerable advances in the treatment of localized disease have been achieved since the introduction of combined modality treatment, increasing the prognosis of overall survival to 70%. Yet, established therapies have only limited success in treating both metastatic disease and nonresponders to primary chemotherapy. Therefore, new therapeutic approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Vorinostat is a histone deacetylases (HDAC) inhibitor and chemically a suberanilohydroxamic acid [12]. HDAC inhibitors are reported for their anti-depressant, anti-epileptic properties and are recommended for neurodegenerative diseases [1].…”
Section: Introductionmentioning
confidence: 99%
“…Vorinostat is a histone deacetylases (HDAC) inhibitor and chemically a suberanilohydroxamic acid [12]. HDAC inhibitors are reported for their anti-depressant, anti-epileptic properties and are recommended for neurodegenerative diseases [1].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the low ICD-risk patients displayed better responses to DMOG, Midostaurin, and Shikonin. Pettke A et al reported that vorinostatin synergistically enhanced the cytotoxicity of doxorubicin and cisplatin in OS, which may be a promising addition to present treatment regimens (48). Midostaurin (PKC412), a derivative of staurosporine, has been proven to induce the apoptosis of Ewing's sarcoma cell lines and significantly suppress xenograft tumor growth (49).…”
Section: Discussionmentioning
confidence: 99%
“…A DNA methyltransferase inhibitor, decitabine, improved the chemosensitivity of OS cells to cisplatin when used together (Chaiyawat et al, 2020), as well as providing an opportunity to promote OS differentiation through expression of the oestrogen receptor ER-α (Osuna et al, 2019). Histone deacetylase inhibitors such as panobinostat, domatinostat, entinostat, vorinostat, trichostatin A and sodium butyrate have been tested alone (Deng et al, 2016;McGuire et al, 2020;Mu et al, 2015;Rao-Bindal et al, 2013;Torres et al, 2020;Xie et al, 2016) or in combination with doxorubicin/cisplatin (Pettke et al, 2016) or decitabine (Capobianco et al, 2014) and have shown anti-proliferative and antimetastatic effect in OS cells. increase in Young's modulus that is accompanied with increased traction forces and spreading area (Lo et al, 2000).…”
Section: Role Of Epigenetic Modificationsmentioning
confidence: 99%